The Sound Absorption Coefficient and Noise Reduction Coefficient of Rice Husk Silica - Tan Ke Wei; Zaleha Mohamad (JSE Journal of Science and Engineering, 2020)
Efficient noise control is neccessary to be applied to reduce the sound pollution and obtain a comfortable life. Rice husk is one of the abandoned agriculture waste material that can obtained in a large quantity which have the potential in the application of sound absorber. Rice husk silica samples have been fabricated in various composition and thickness by using epoxy and methyl ethyl ketone peroxide (MEKP) as binder. Impedance tube testing and physical test are conducted to obtain the properties of rice husk silica. The result found that specimens with higher composition of rice husk silica and using MEKP as binder have the lowest density, highest porosity and give a better sound absorption coefficient. The increment of thickness can produce a greater sound absorption at lower frequency. The results also demonstrate 20mm is the best thickness for a greater noise reduction coefficient.